Pregnancy in a Patient with Idiopathic Pulmonary Fibrosis: A Case Report - Rebecca Horgan; Zeinab Kassem; Gloria Too; Alfred Abuhamad; Steven Warsof (American Journal of Perinatology Reports, 2023)
Abstract Idiopathic pulmonary fibrosis (IPF) is a progressive restrictive lung disease. Data on the impact of pregnancy on IPF and maternal outcome is extremely limited. We present the case of a 35-year-old woman, gravida 1 para 0 with familial IPF with no oxygen requirement prior to pregnancy. The patient demonstrated significant deterioration in her lung function beginning at 22 weeks' gestation and underwent hospitalization at 272/7 weeks gestation due to acute on chronic hypoxic respiratory failure, ultimately requiring delivery at 28 weeks' gestation. The patient has not regained her baseline pulmonary function and remains oxygen dependent at 5 months postpartum. Based on limited available data, significant maternal morbidity and mortality is reported for women with IPF who become pregnant.